Profil Kondisi Fisik Pemain Ssb Tiku Putra Kecamatan Tanjung Mutiara Kabupaten Agam Dimasa Pandemi Covid-19 - Bagus Getra Karyanto; Anton Komaini; Windo Wiria Dinata (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The problem in this research is that the physical condition of SSB Player Tiku Putra Of Tanjung Mutiara District of Agam Regency is not yet known. This research aims to find out the physical condition of SSB Tiku Putra players of Tanjung Mutiara District of Agam Regency. This type of ressearch is descrriptive. The reseaarch was conductted on October 12, 2021 in Mahogany Tiku Field, Tanjung Mutiara District, Agam Regency. The population is all SSB Tiku Putra players as maany as 18 people. Sampliing technique is total samplling, which is as many as 18 people. The research instruments in this study are: 1) Yo-Yo intermittent recovery test to measure endurance, 2) Standing broad jump to measure the explosiveness of leg muscles, 3) Sprint 30 m to measure speed, 4) Zig-zag run test to measure agility, 5) Foot coordination test to measure ankle coordination. The results of the research of SSB Tiku Putra Players of Tanjung Mutiara District of Agam Regency showed that 1) The average Aerobic Endurance Ability is 41.99 ml / kg / min classified as a moderate category. 2) The explosive ability of the average limb is 255 cm classified as a very good category. 3) The average speed ability is 4.8 seconds classified as less category. 4) The average Agility ability is 26.8 seconds classified as a medium category. 5) Eye Coordination ability owned by players with a value of 8.41 is classified as less category at all. 6) The ability of physical condition owned by the player is with a value of 249 classified as a medium category